The Blackwell companion to criminology - Sumner, Colin (Blackwell companions to sociology., 2004)
Provides a contemporary and global resource to scholarship in both classical and topical areas of criminology. The essays focus on major issues in criminology today, commenting upon key debates and theories, outlining the implications of new studies, and discussing contemporary developments.